2016
DOI: 10.1016/j.renene.2015.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Investigating two-phase digestion of grass silage for demand-driven biogas applications: Effect of particle size and rumen fluid addition

Abstract: a b s t r a c tHigh lignocellulose content grass silage was investigated for two-phase digestion (leaching followed by upflow anaerobic sludge blanket (UASB)) for application to demand-driven biogas production. Leaching trials were undertaken investigating the effects of particle size reduction and rumen fluid addition on the hydrolysis and acidogenesis phases. Reducing grass silage particle size to <1 cm was not suited to leaching as particles could not be fully entrained in the system; this was not an issue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…As the hydrolysate mainly consists of readily degradable material, methane production can be raised within hours [15,49]. On-demand production of biogas was also shown for the lignocellulosic substrate grass silage by operational changes in recirculation [51].…”
Section: Microbial Hydrolysis In a Separate Stagementioning
confidence: 95%
“…As the hydrolysate mainly consists of readily degradable material, methane production can be raised within hours [15,49]. On-demand production of biogas was also shown for the lignocellulosic substrate grass silage by operational changes in recirculation [51].…”
Section: Microbial Hydrolysis In a Separate Stagementioning
confidence: 95%
“…Researchers already investigated the potential of flexible biogas production and/or biogas storage using flexible feeding patterns of the feedstock for the AD. For example the potential of a two-phase digestion of grass silage to be used as a demand-driven system is investigated and it is concluded that it might offer advantages [37]. Recently, Zealand et al (2017) analyzed the effect of feeding frequency and organic loading rate on biomethane production [38].…”
Section: Discussionmentioning
confidence: 99%
“…The particle size must also be considered, as it may hinder or benefit microorganisms access due to the available contact area (WALL et al 2016), as well as the proper adjustment of the ratio between forage and manure, which can increase or decrease favorable conditions to degradation (PRAPINAGSORN et al 2017).…”
Section: Introductionmentioning
confidence: 99%